Liver alanine catabolism promotes skeletal muscle atrophy and hyperglycaemia in type 2 diabetes - Okun, Jürgen G.; Rusu, Patricia M.; Chan, Andrea Y.; Wu, Yuqin; Yap, Yann W.; Sharkie, Thomas; Schumacher, Jonas; Schmidt, Kathrin V.; Roberts-Thomson, Katherine M.; Russell, Ryan D.; Zota, Annika; Hille, Susanne; et al. (Nature metabolism, 2021)
Both obesity and sarcopenia are frequently associated in ageing, and together may promote the progression of related conditions such as diabetes and frailty. However, little is known about the pathophysiological mechanisms underpinning this association. Here we show that systemic alanine metabolism is linked to glycaemic control. We find that expression of alanine aminotransferases is increased in the liver in mice with obesity and diabetes, as well as in humans with type 2 diabetes. Hepatocyte-selective silencing of both alanine aminotransferase enzymes in mice with obesity and diabetes retards hyperglycaemia and reverses skeletal muscle atrophy through restoration of skeletal muscle protein synthesis. Mechanistically, liver alanine catabolism driven by chronic glucocorticoid and glucagon signalling promotes hyperglycaemia and skeletal muscle wasting. We further provide evidence for amino acid-induced metabolic cross-talk between the liver and skeletal muscle in ex vivo experiments. Taken together, we reveal a metabolic inter-tissue cross-talk that links skeletal muscle atrophy and hyperglycaemia in type 2 diabetes.
Gesehen am 11.07.2021